A working day in the life of employees: development and validation of the scale for daily hassles and uplifts at work - Junça Silva, A.; Caetano, A.; Lopes, M. (TPM - Testing, Psychometrics, Methodology in Applied Psychology, 2020)
This paper describes the development and validation of the scale for daily hassles and uplifts at work (SDHUW) in three studies. The SDHUW is a 50-item scale that measures two types of affective daily events in the workplace – daily hassles and uplifts - including the frequency and intensity of those events. The SDHUW was tested for its factor structure, reliability and convergent validity. Moreover, we tested whether daily hassles and uplifts would predict work attitudes (work engagement and job crafting) and psychological states (stress, anxiety and depression). The scale measures five daily hassle dimensions: conflicts and unpleasant interactions, time management and task-related hassles, threats to self-efficacy and performance, failures, interruptions and annoyances, and organizational and leader-related hassles; and five daily uplift dimensions: achievement, recognition and task-related uplifts, pleasant interactions, helpfulness and compliments, humor and communication, time management and costumer-related uplifts and organizational uplifts. The SDHUW showed convergent validity and reliability. It correlates with positive and negative affect, job-satisfaction, work-engagement, well-being, job crafting, and mental health outcomes.